Blending Technology and Tradition: PjBL in ELT to Foster Self-Directed Learning - Sukmawati, Sukmawati; Rosmayanti, Vivit; Amin, Sulvahrul (Universitas Negeri Makassar, 2025)
The integration of technology in education has revolutionized the way students learn, offering unprecedented opportunities for fostering self-directed learning (SDL). This study explores the implementation of Project-Based Learning (PjBL) that blends technological tools with local wisdom-based educational practices to enhance self-directed learning among students. This study employed a qualitative research design. Thematic Analysis (TA) was used to analyze the data with the help of Nvivo R14 software. Participants were senior high school teachers from South Sulawesi, Indonesia, who engaged in PjBL integrated with technology and local wisdom. The data were gathered through interviews and observations, with a focus on the integration of PjBL, technology, and local wisdom in learning. The findings identified four primary themes such as PjBL procedures, technology integration, local wisdom integration, and impact on students’ SDL. Each of the primary themes is supported by some subthemes. The findings of this study have three practical implications. First, incorporating local wisdom into ELT helps preserve cultural heritage while making learning more meaningful and relatable for students. Second, integrating technology and local wisdom into PjBL can enhance student engagement and motivation, the project from familiar cultural contexts alongside interactive technological tools makes learning more appealing and enjoyable. Furthermore, applying technology-integrated local wisdom project-based learning facilitates students’ SDL. The students have opportunities to take ownership of their learning process as well as develop their collaboration skills, critical thinking, learning independence, language competence, and cultural understanding. Finally, the researchers expected this study to provide a more comprehensive understanding of how local cultural content may be applied to English language teaching.